2003
DOI: 10.1359/jbmr.2003.18.7.1206
|View full text |Cite
|
Sign up to set email alerts
|

Dietary n-3 Fatty Acids Decrease Osteoclastogenesis and Loss of Bone Mass in Ovariectomized Mice

Abstract: The mechanisms of action of dietary fish oil (FO) on osteoporosis are not fully understood. This study showed FO decreased bone loss in ovariectomized mice because of inhibition of osteoclastogenesis. This finding supports a beneficial effect of FO on the attenuation of osteoporosis.Introduction: Consumption of fish or n-3 fatty acids protects against cardiovascular and autoimmune disorders. Beneficial effects on bone mineral density have also been reported in rats and humans, but the precise mechanisms involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
221
1
3

Year Published

2006
2006
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 261 publications
(248 citation statements)
references
References 89 publications
23
221
1
3
Order By: Relevance
“…In an elegant study Cohen et al [114] reported data that IL-10(anti-inflammatory) knock-out mice fed flax seed oil, providing ALA, had significantly lower serum levels of TNF-α and higher bone density compared to IL-10 knock-out mice fed corn oil that is rich in omega-6 fatty acids. The difference in bone density was possibly partly due to the reduction in TNF-α by feeding of ALA. Downregulation of resorptive cytokines such as TNF-α and IL-6 by n-3 PUFA in OVX mice was also reported by other research groups [115,116]. Thus dietary modulation by increasing n-3 PUFA intake could affect the generation of IL-1, IL-6 and TNF-α which in turn could modulate bone health.…”
Section: Effects Of Polyunsaturated Fatty Acids and Metabolites On Cysupporting
confidence: 63%
See 2 more Smart Citations
“…In an elegant study Cohen et al [114] reported data that IL-10(anti-inflammatory) knock-out mice fed flax seed oil, providing ALA, had significantly lower serum levels of TNF-α and higher bone density compared to IL-10 knock-out mice fed corn oil that is rich in omega-6 fatty acids. The difference in bone density was possibly partly due to the reduction in TNF-α by feeding of ALA. Downregulation of resorptive cytokines such as TNF-α and IL-6 by n-3 PUFA in OVX mice was also reported by other research groups [115,116]. Thus dietary modulation by increasing n-3 PUFA intake could affect the generation of IL-1, IL-6 and TNF-α which in turn could modulate bone health.…”
Section: Effects Of Polyunsaturated Fatty Acids and Metabolites On Cysupporting
confidence: 63%
“…LCPUFAs have been shown to affect cellular proteins and receptor activator of nuclear factor κβ (RANK), a receptor found on the osteoclast which controls osteoclastogenesis. This will be discussed in detail below [25][26][27].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Polyunsaturated fatty acids (PUFAs) have been implicated in bone homeostasis both in vitro [1][2][3] and in vivo. [4][5][6][7][8] There is increasing evidence that lack of certain PUFAs in the diet can induce bone loss, [9][10][11] while dietary supplementation of some PUFAs has been shown to be beneficial for bone.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 A recent study by Högstrom et al 14 demonstrated that n-3 fatty acids, particularly docosahexaenoic acid (DHA), are positively associated with bone mineral accrual, and thus, with peak bone mineral density in healthy young men. Some in vivo studies have shown that supplementation with PUFAs such as GLA, EPA, and DHA, could decrease bone turnover in ovariectomized animals by decreasing bone resorption 3,5 while others have shown that n-3 PUFA treatment in rats could result in greater bone formation rates. 2 Some suggested mechanisms of action for the PUFAs in these models include the following: modulation of calcium absorption from the intestine, increased bone mineralization, enhancement of bone collagen synthesis, and reduction of urinary calcium excretion, thereby increasing the pool of available calcium for bone mineralization in the body.…”
Section: Introductionmentioning
confidence: 99%